Exploiting observations and measurement data standard for distributed LTER-Italy freshwater sites. Water quality issues. - Lanucara,Simone; Carrara,Paola; Oggioni,Alessandro; Rogora,Michela; Kamburska,Lyudmila; Rossetti,Giampaolo (PeerJ Preprints, 2016)
Water quality is a multi-source, multi-purpose problem that needs exploiting observations, often taken by a number of heterogeneous bodies. This problem has been tackled within the Italian Long Term Ecological research network (LTER-Italy) in an experiment aimed at testing how ecological observations of mountain lakes water can be shared by OGC (Open Geospatial Consortium) standard services of the Sensor Web Enablement (SWE) initiative. A friendly and easy implementation of these services is fostered by the usage of the open source software Geoinformation Enabling Toolkit StarterKit ® (GET-IT). It has been used in the experiment to create SOS services, upload observations and create SensorML metadata of the involved sensors. This contribution describes the experiment and presents its results.
Keywords: Sensor Web Enablement; Spatial Data Infrastructure; Ecological research; Free and Open Source Software for Geospatial